RESILIENCE AND PHYSIOLOGICAL RESPONSES OF THE DOMESTICATED ASIAN REDTAIL CATFISH Hemibagrus nemurus TO HYPOXIA CONDITION - Iswantari, Aliati; Kurniawan, Kurniawan; Prakoso, Vitas Atmadi; Radona, Deni; Irawan, Deni; Putri, Fera Permata; Cahyanti, Wahyulia; Arifin, Otong Zenal; Subagja, Jojo; Gustiano, Rudhy; Kusmini, Irin Iriana; Wibowo, Arif; Kristanto, Anang Hari (Indonesian Aquaculture Journal, 2023)
Hypoxia is one of the critical issues in aquaculture production systems as it can lead to physiological disturbances in cultured fish. This research aimed to evaluate the tolerance level and physiological responses of domesticated Asian redtail catfish Hemibagrus nemurus reared in various hypoxia conditions. A total of 12 fish/treatment were acclimated to gradually decreased dissolved oxygen treatments until fish experienced aquatic surface respiratory (ASR) and loss of equilibrium (LOE). Cortisol, haemoglobin, and glucose levels were detected in the blood plasma to evaluate the stress response of the fish to hypoxia. The result showed that ASR of H. nemurus was identified at 2.17 ± 0.14 ppm of dissolved oxygen (DO) concentration with the percentage of ASR was 77.67 ± 9.53%, while LOE critical of H. nemurus happened at 0.63 ± 0.15 ppm of DO where 55.56 ± 4.81% of the fish experienced LOE. There were significant differences in the values of physiological parameters (blood cortisol, haemoglobin, and glucose) between control and treatments as fish experienced LOE (P<0.05). In the present  study, it was found that the Asian redtail catfish is classified as a hypoxia-sensitive fish group. Tehis finding is valuable information for the rearing and growing of the fish to provide an optimal DO concentration for their growth and survival.